Tingkat Ketergantungan Masyarakat Terhadap Hutan (Studi Kasus Kawasan Hutan Koa Besipae, Desa Mio, Kecamatan Amanuban Selatan, Kabupaten Timor Tengah Selatan) - Akwilin Nay; Mamie E. Pellondo’u; Nixon Rammang (Wana Lestari, 2023)
The problem of poverty in the community around the forest is a type of problem that is often found in forest management in Indonesia. Communities around the forest have a dilemmatic position about the forest. On the one hand, they are the people who play the most role in the context of forest conservation. On the other hand, their average condition is poor and they need support in meeting their various needs. This condition also happens to the people who are living around the Koa Besipae Forest area, Mio Village, South Amanuban District, South Central Timor Regency. The location of this research is located in Mio Village, South Amanuban District, South Central Timor Regency, with the 35,43 Km² village areas, this study was conducted to determine how much the community’s dependence on the Koa Besipae Forest Area, Mio Village, South Amanuban District, South Central Timor Regency. This research was conducted on June 2022. The number of the respondents in this research are 20 people which obtained by using purposive sampling method and analyzed by using quantitative analysis. The results of the research which obtained through the interview method with the help of questionnaires and direct observation method shows the level of dependency of the community’s economic income on the Koa Besipae Forest Area in the high category of 95,45% which is determined by the variable level of dependency (66,67% - 100%).